The aerodynamics analysis of type UAV aircraft with pusher engine configuration by use of DATCOM software - Al Aian, Ahmad Eshtiwey (2011)
In line with the advancement of micro processor technology, availability small scale aircraft engine model, light weight material and also better understanding in the aircraft design process had brought a current attention to develop autonomous flying vehicles. This kind of vehicle has offered various applications, such as military and civilian purposes. However to develop such kind autonomous flying vehicles one have to develop a control law which govern how the flying vehicle to fly. To do so one have to prepare firstly the required aerodynamics data. The present work focused on the type of flying vehicle powered by electric type of engine. This type of engine is normally available in the market is at the size of engine less than 5 hp. Due to the engine limitation, the size of flying vehicle. has been decided to the aircraft configuration with all required devices for autonomous they vehicle is no more than 6 Kg. through series of aerodynamics assessment aircraft components (fuselage, wing, airfoil on the control surface and it's high lift devices). the present special write produce an initial aircraft configuration with aerodynamic data which can be future studied for development that aircraft as an autonomous flying vehicle.